(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Laicità necessaria - 2. Il Cristianesimo: una fede scandalosa - 3. La maggiore età del mondo - 4. Ritrovare Dio da adulti - 5. Provvisorietà dell’etica cristiana - 6. Führer e Verführer: lo scambio delle vesti e la fragilità del male. Secularism as requirement of reason: the actuality of Dietrich Bonhoeffer ABSTRACT: Dietrich Bonhoeffer is a very significant figure of the Protestant theology. Having experienced the most dramatic period of the German history he is well remembered as “resistant” to the National Socialism, but he deserves also to be reconsidered because of his defense, as believer, of the value of “secularism”, necessary to safeguard an authentic profession of faith.